Manajemen Program Pembelajaran Bahasa Arab dengan Metode Langsung (Direct Method) di Pondok Tahfidz Putri Darul Mubarok Curup (DMC) - Rahmad Arif Setiawan; Nuril Mufidah (Mahira: Journal of Arabic Studies & Teaching, 2023)
This study determines the management of teaching arabic language with direct method, this study uses qualitative descriptive with analysis method’s huberman and miles which is data display, data analysis, data reduction and conclusion. This study answering the question, those are; 1) How management of the arabic language learning program using the direct method (direct method) at the pondok tahfidz putri daarul mubarak curup (dmc)? 2) What are the supporting factors and inhibiting factors in the management of the Arabic language learning program using the direct method at the Pondok Tahfidz Putri Daarul Mubarak Curup (DMC)?. The results of this study include several things; 1) The implemented management of the arabic language learning program using the direct method (direct method) at the pondok tahfidz putri daarul mubarak curup (dmc) based on 4 management functions namely; a. Planning function: In planning Arabic learning the teacher prepares a Lesson Plan (RPP) which includes equipment or auxiliary media to facilitate the Arabic learning process, while also preparing a number of questions about material that has previously been taught to recall the lessons that have been taught, this can also improve students' cognitive abilities with the drill method used by the teacher when asking indirectly questions that are routinely given and continuously related to the lessons that have been taught, b. Organizing function: In the process of organizing learning the Arabic teacher at the tahfidz Putri Daarul Mubarok Curup Islamic boarding school organizes learning by managing the time when teaching, inviting students to ask questions, conducting questions and answers, determining activities and materials, paying attention to start and finish times of learning, the process of organizing learning These are arranged systematically to make it easier for teachers to carry out learning activities. c. Implementation function: The Arabic teacher at Pondok Tahfidz Putri Daarul Mubarok Curup carries out the function of implementing Arabic learning with the following stages: 1. Pre-instructional stage; The teacher greets the students by saying "Assalamu'alaikum", followed by greetings in Arabic in the form of: كَيْفَ حَالُكُم؟، نَهَارُكُمْ سَعِيْدَة؟،صَبَاحُ الخَيْر؟, then the teacher asks about the previous lesson (الدُّرُوسُ السَّابِقَةُ ؟); The teacher prepares the material carefully, looks for a method that fits the material to be delivered to students, prepares questions for each material, explains the learning objectives, writes the subject matter on the blackboard, 3. Evaluation and follow-up stage; evaluate by giving practice questions in the book as formative tests, as well as conducting daily exams and conducting summative tests which are carried out at the end of the semester. d. Supervision function: In supervising the school principal towards teachers, especially teachers in learning Arabic at the Daarul Mubarok Curup daughter's tahfidz boarding school, the school principal supervises by collecting the necessary data from planning, implementation and evaluation of learning Arabic. These data were collected and evaluated as a whole and given follow-up on the evaluation. This was done by the school principal as a form of supervision of learning Arabic and improving the quality of learning carried out by Arabic teachers.2) Supporting factors and inhibiting factors in the management of the Arabic language learning program using the direct method (Direct Method) at the Tahfidz Putri Daarul Mubarak Curup (DMC) were found including: A) Supporting factors; 1. From the student side. Enthusiasm of students is quite high in learning Arabic with the direct method, 2. In terms of student learning methods. The learning method used in learning Arabic at Pondok Tahfidz Putri Daarul Mubarok Curup Putri makes it easy for students to understand and master lessons, 3. From the side of the teacher/teaching staff. The ustadzah who teaches at Daarul Mubarok Curup Putri Tahfidz Putri Islamic Boarding School is an alumnus of the Gontor Islamic Boarding School, and the others are graduates of Islamic boarding schools who are very closely related to Arabic, 4. From an environmental standpoint. The bi'ah lughawiyah system (creating an environment with Arabic nuances) implemented at the Tahfidz Putri Daarul Mubarok Curup boarding school system. B) Inhibiting factors; The inhibiting factor experienced by the Arabic language teacher at Putri Daarul Mubarok Curup's tahfidz boarding school is that the lessons that have been taught are often forgotten by female students so that the teacher must continue to repeat previous lessons in a concise and clear manner for efficiency in teaching time.